Exploration of Gene Action Conditioning Tolerance to Aluminum (Al) Toxicity in Tropical Maize - Ndeke, Victoria; Tembo, Langa (Contemporary Research and Perspectives in Biological Science Vol. 1, 2024)
Maize is the third most important cereal crop in the world after wheat and rice. In Zambia, maize production has been reported to be increasing but its production is however hampered by both biotic and abiotic factors. Among the abiotic factors, Aluminum (Al) toxicity causes high yield losses and is directly linked to acidic soils. The application of lime can ameliorate this problem, but it is expensive for small-scale farmers. Developing maize varieties that are tolerant to Al toxicity is cheaper and feasible for small-scale farmers. The purpose of this research was to investigate the type of gene action conditioning tolerance to aluminum toxicity in tropical maize. The maize samples were obtained from the Zambia Agriculture Research Institute (ZARI). Eleven inbred lines were mated in an 8 male (4 moderately tolerant and 4 susceptible) x 3 female (resistant) North Carolina Design II. The seeds were germinated on petri dishes lined with filter paper wetted with water and placed in the germination chamber for 5 days at 25oC. The genotypes were evaluated on the 11th day. The shoot and root lengths were measured immediately after harvesting using a 30 cm ruler. Analysis of variance on root length, shoot length, number of root hairs, and root biomass was performed using a fixed model in the GenStat statistical package. Results revealed that general combining ability (GCA) effects due to both males and females were highly significant (P\(\le\) 0.001) for root biomass. The shoot length GCA effects due to both males and females respectively were significant (P\(\le\) 0.01). Similarly, the GCA effects due to females and males for root length were significant, P\(\le\) 0.01 and P\(\le\) 0.05 respectively. The genotype CML 511 had the most desirable significant GCA effect value (1.40) for root length among the male lines while CML 538 had the most desirable significant GCA effect value (0.92) among the female lines. The baker’s ratio for root length was found to be 0.49 implying that both additive and non-additive gene action was important in conditioning aluminum toxicity tolerance in tropical maize. Further work on petri studies under controlled environments and finally field conditions with additional parameters examined, such as leaf area, stress hormones, and antioxidant enzyme levels can generate more informative knowledge.